Performance Comparison of Various Substrates on a Wearable Ultra-Wideband Antenna - Idzhar, R. F. H. R.; M. Shah, S.; A. Majid, H.; Musa, U.; Suriani, N. S. (International Journal of Integrated Engineering, 2024)
The substrate between the patch and ground plane of microstrip antenna plays an important role in antenna design as it dictates the linear characteristics performances of the antenna. This work focusses on the comparison between three UWB antennas fabricated on different substrate materials which are Rogers Duroid RO3003™ with a dielectric constant, ?r of 3, loss tangent, tan ? of 0.010 and thickness, h of 1.52 mm; denim substrate with ?r of 1.7, tan ? of 0.07 and h of 0.7 mm; and felt substrate with ?r of 1.3, tan ? of 0.02 and h of 1.1 mm. From the comparison, felt substrate offers a good antenna’s performance in terms of frequency range, bandwidth, gain and efficiency followed by Rogers Duroid RO3003™ and denim substrates. The simulation results show that the frequency range of the UWB antenna with felt substrate is from 2.31 GHz to 11.74 GHz with a bandwidth of 9.43 GHz; gain, G of 5.489 dBi; and efficiency, ? (%) of 91 %. The UWB antenna fabricated on RO3003™ has a frequency range from 2.94 GHz to 12.25 GHz with a bandwidth of 9.28 GHz, gain of 5.323 dBi and efficiency of 90%. Lastly, the antenna with denim substrate observed a frequency range from 2.67 GHz to 9.99 GHz with a bandwidth of 7.23 GHz, gain of 5.198 dBi and efficiency of 81.68%. The bending investigation are performed for each UWB antenna with different diameters (d = 50 mm, 80 mm and 100 mm) of vacuum cylinder in CST MWS® software and PVC pipes during measurement. It can be concluded from the simulated and measurement results that the performance of the antennas are not affected under bending condition and suitable to be worn on body for wearable applications.